Honey healing: A sweet solution to alleviate diarrhea and curb bowel movement frequency in children - Qaromah, Yafiana; Nugroho, Sri Hananto Ponco; Sulistyono, Dwi (Universitas Muhammadiyah Magelang, 2024)
Diarrhea is the second leading cause of death among children under five years of age. It can persist for an extended period, leading to dehydration and potential malnutrition. While the literature presents various complementary therapies for managing diarrhea, there is a notable lack of studies specifically addressing the use of honey to mitigate hyperactivity of bowel movements in affected patients. Therefore, the objective of this study was to evaluate the benefits of honey in children experiencing diarrhea. The study involved two pediatric patients who were administered pure honey over a two-day period. The dosage consisted of 5 cc of honey mixed with 10 cc of water, given three times daily at 07:00, 17:00, and 21:00. The honey used in the study was confirmed to be pure. The findings suggest that pure honey is effective in reducing the frequency of bowel movements in children with acute diarrhea. This conclusion is supported by the observed outcomes in both patients, which indicated a reduction in bowel movement frequency following the administration of honey. Consequently, it is recommended that pure honey be considered as a complementary treatment for children suffering from acute diarrhea. Keywords: Children care; diarrhea; honey treatment; innovation in health; medication